Pengaruh Kompensasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Puskesmas Bantarsari - Adam Triana Irawan; Mila Karmila; Rita Tri Yusnita (Global Leadership Organizational Research in Management, 2023)
This study aims to determine the effect of compensation and work discipline simultaneously or partially on the performance of Bantarsari Puskesmas employees. The method used in this research is quantitative with a survey approach. With a research sample of 45 people as respondents to the Bantarsari Puskesmas based on 45 known population data. The data used is primary data. The analytical tool used in this study is multiple linear regression using the SPSS version 25 support application. Simultaneously compensation and work discipline have a significant effect on employee performance. Partially, the compensation variable has a significant effect on employee performance, as well as the work discipline variable, which partially has a significant effect on employee performance.